1988
DOI: 10.1002/cyto.990090109
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of simian virus 40 infection of CV‐1 cells by quantitative two‐color fluorescence with flow cytometry

Abstract: Key terms: DNA content changes, permissive infection, viral antigens, T-antigen, V-antigen Considerable interest has been generated in the analysis of gene products obtained from both viral and cellular oncogenes, since these genes may be responsible for such activities as cell proliferation, differentiation, and the acquisition of the neoplastic phenotype (1). Simian Virus 40 (SV40) has been an important model system for studies of viral replication, viral transformation, and gene regulation (14,20,22). The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…All cultures were maintained at 37°C in a humidified 5% CO 2 incubator. SV40 wild-type (wt) strain RH911 and small t mutant strain dl888 were grown and plaque assayed on CV-1 cells as previously described (35,70). The SV40 small t mutant dl888 was provided by Kathleen Rundell.…”
Section: Cells and Virus African Green Monkey Kidney (Cv-1) Cells (Amentioning
confidence: 99%
See 1 more Smart Citation
“…All cultures were maintained at 37°C in a humidified 5% CO 2 incubator. SV40 wild-type (wt) strain RH911 and small t mutant strain dl888 were grown and plaque assayed on CV-1 cells as previously described (35,70). The SV40 small t mutant dl888 was provided by Kathleen Rundell.…”
Section: Cells and Virus African Green Monkey Kidney (Cv-1) Cells (Amentioning
confidence: 99%
“…The infected cells progress through G 1 , S, and G 2 phases but do not enter mitosis (17,35,58). Rather, the DNA content of the infected cells increases beyond 4C (defined as ϾG 2 phase) because of replication of both viral and cellular DNA.…”
mentioning
confidence: 99%
“…In SV40-infected cells, mitomycin C treatment leads to an increase in a 5S form of DNA ligase thought to be involved in DNA repair (36). Lytic infection by SV40 results in G 2 arrest and a negative regulation of CDC2 by CHK1, a checkpoint kinase downstream of ATR (ATM-Rad3-related kinase) (30,38). The SV40 T antigen disrupts nuclear DNA repair foci containing MRE11 and interacts with NBS1, a target of ATM (ataxia telangiectasia mutated) and an essential factor in the S-phase checkpoint that senses DNA damage (14,51).…”
mentioning
confidence: 99%
“…S phase in lytically infected cells is not followed by G2 phase and mitosis, but rather by continued DNA synthesis and an increase in overall cellular DNA content (3). Several experimental approaches demonstrated that the DNA synthesized in cells with DNA content >4C is a combination of viral and host cell DNA.…”
mentioning
confidence: 99%